2017
DOI: 10.1002/pbc.26629
|View full text |Cite
|
Sign up to set email alerts
|

Association of outcomes and anti‐Xa levels in the treatment of pediatric venous thromboembolism

Abstract: There was no statistically significant difference between low-range versus high-range mean anti-Xa levels and thrombus resolution. Empiric clinical practices of targeting anti-Xa levels in the higher therapeutic range to achieve better outcomes may not be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This would suggest that the clinically effective concentration may be lower than the purported therapeutic guidelines. 32 This confirms the findings in several case reports and single-center studies, 4,33 which found recommended dosing of 1.5 mg/kg/dose every 12 hours to be inadequate to achieve desired therapeutic response. The dosage for our patient began at 2 mg/ kg every 12 hours and was increased to a high of 3.49 mg/kg every 12 hours.…”
Section: Discussionsupporting
confidence: 86%
“…This would suggest that the clinically effective concentration may be lower than the purported therapeutic guidelines. 32 This confirms the findings in several case reports and single-center studies, 4,33 which found recommended dosing of 1.5 mg/kg/dose every 12 hours to be inadequate to achieve desired therapeutic response. The dosage for our patient began at 2 mg/ kg every 12 hours and was increased to a high of 3.49 mg/kg every 12 hours.…”
Section: Discussionsupporting
confidence: 86%
“…In all cases, resolution/recurrence rate was more positive than TTR achievement rate. 29,[32][33][34][35][36] Further, there was no association between anti-factor Xa level and bleeding.…”
Section: Lmwhmentioning
confidence: 99%
“…The optimal scheduling of anti-factor Xa assays in children receiving LMWH has received surprisingly little attention, with no article clearly outlining a preferred schedule. 29,32,34 It appears that many studies have performed monitoring of anti-factor Xa assays daily or twice daily until the LMWH is therapeutic and then weekly thereafter with reducing frequency if the patient remained therapeutic or stable and in the absence of renal impairment. The practicalities of being able to draw blood often further reduce the frequency of monitoring.…”
Section: Lmwhmentioning
confidence: 99%